Assessment of diclofenac LC50 reference values in juvenile and embryonic stages of the zebrafish (Danio rerio) - Prášková, Eva; Voslářová, Eva; Široká, Zuzana; Plhalová, Lucie; Mácová, Stanislava; Maršálek, Petr; Pištěková, Vladimíra; Svobodová, Zdeňka (Polish journal of veterinary sciences, 2011)
The aim of the study was to compare the acute toxicity of diclofenac to juvenile and embryonic stages of the zebrafish (Danio rerio). Acute toxicity tests were performed on the aquarium fish Danio rerio, which is one of the model organisms most commonly used in toxicity testing. The tests were performed using a semi-static method according to OECD guideline No. 203 (Fish, acute toxicity test). Embryo toxicity tests were performed in zebrafish embryos (Danio rerio) in compliance with OECD No. 212 methodology (Fish, short-term toxicity test on embryo and sac-fry stages). The results were subjected to a probit analysis using the EKO-TOX 5.2 programme to determine 96hLC50 and 144hLC50 (median lethal concentration, 50% mortality after a 96 h or 144 h interval, respectively) values of diclofenac. The statistical significance of the difference between LC50 values in juvenile and embryonic stages of Danio rerio was tested using the Mann-Whitney non-parametric test implemented in the Unistat 5.1 programme. The LC50 mean value of diclofenac was 166.6 +/- 9.8 mg/L in juvenile Danio rerio, and 6.11 +/- 2.48 mg/L in embryonic stages of Danio rerio. The study demonstrated a statistically higher sensitivity to diclofenac (P < 0.05) in embryonic stages compared to the juvenile fish.
Keywords: dánio pruhované; diklofenak; vztah mezi dávkou a účinkem léčiva; LD50; embryo nesavčí; Animals; Embryo, Nonmammalian; Lethal Dose 50; antiflogistika nesteroidní; Diclofenac; Zebrafish; Anti-Inflammatory Agents, Non-Steroidal; zvířata; Dose-Response Relationship, Drug